144k views
2 votes
9x+2y=39 6x+13=-9can u help me solve this equation?

1 Answer

2 votes

9x+2y=39

6x+13y = -9

multiply the first by 2 and the second by 3

18x + 4y = 78

18x + 39y = -27

Subtract the second from the first

4y - 39y = 78 - -27

-35y = 78 + 27

-35y = 105

Divide both sides by - 35

y = -3

substituting into the second equation

6x + 13(-3) = -9

6x - 39 = -9

collect like terms

6x = -9 + 39

6x = 30

Divide both sides by 6

x = 5

Hence

(x,y) = (5, -3)

User Sujit Kumar Singh
by
5.3k points